A new cave species of Coecobrya Yosii (Collembola, Entomobryidae, Entomobryinae) from South Africa, with an identification key to the genus - Cipola, Nikolas Gioia; Bellini, Bruno Cavalcante (Zootaxa, 2016)
Coecobrya anaguilae sp. nov., a new species of springtail from Cango Caves, South Africa is described and illustrated. The new species is similar to other species of tenebricosa-group such as C. communis (Chen & Christiansen), C. edenticulata (Handschin), and C. tropicalis Qu, Chen & Greenslade in some elements of dorsal chaetotaxy, absence of eyes, unguis with one unpaired median tooth, and manubrium without smooth chaetae, but differs from them in dorsal head, mesothoracic and collophore chaetotaxy. This is the first species of Coecobrya described from Africa as well as the first indisputable record of the genus for the whole continent. In this study an updated key to the species of the genus is provided, adding 14 species to the most recently published identification key. We also discuss some aspects of distribution and evolution of Coecobrya.